EVALUASI KONSUMSI ZAT GIZI TERHADAP WANITA USIA MENOPAUSE > 49 TAHUN DI POSYANDU-POSYANDU LANSIA KABUPATEN ROKAN HULU - Herawati, Rika (Jurnal Martenity and Neonatal, 2015)
Menopause is known as the end of menstruation or menstrual period, and is often considered a scourge in the lives of women. Most women begin to experience symptoms of menopause at over 40s and reached its peak at the age of 50 years. According to the calculations of scientists in 2030 estimated the number of women in the world who entered menopause will reach 1.2 billion people. That means a total of 1.2 billion women will enter the age of over 50 years, and that figure is triple the 1990 census figures on the number of postmenopausal women (Siswono 2001). Objective: To obtain Nutrients consumed To determine the relationship of women and nutrients consumed by women of the age of menopause. Research Methods Quantitative Analytic research with this type of design Analytical Cross Sectional Study, the data retrieval is done Sampling saturated, which amounted to 359 people. Results: The results of the univariate analysis of independent variables with a nominal scale and ordinal shown obtained the consumption of staple foods daily containing carbohydrates as many as 98 people (98%) and Non Carbohydrates 2 (2%), Distribution of respondents vegetable consumption was 98 ( 98%), no consumption of vegetables by 2 people (2%), Distribution of respondents who consume Lauk-Pauk animal protein 34 (34%), and the consumption of protein Vegetable 66 people (66%), distribution of consumption Food additives as many as 87 people (87%) and no consumption of 13 people (13%), distribution of beverages in the healthy beverage consumption of 100 (100%) and drink unhealthy 0%. Analisisi resume bivariate results for the dependent and independent variables with the scale ratio as follows: all of the variables associated with menopause with the strength of the relationship was between the range of 0.344 to 0.400 and all significant variables with P values <0.05. Conclusion The average age of menopause in 100 postmenopausal women in the IHC-IHC Elderly Rokan Hulu in 2013 ie 48.06 causal tahun. Variabel related to the age of menopause is variable carbohydrate consumption of staple foods, consumption of vegetables, side dishes Consumption -pauk animal and vegetable, fruit consumption, the consumption of extra food and healthy beverage consumption.